Perception of Vulnerability to HIV Infection to Consistence of Condoms Use In transgender Sex Workers - Rauf, Dian Ardyanti; Pramono, Joko Sapto; Chifdillah, Nino Adib (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2023)
Transgender is a group with a high risk of HIV AIDS transmission due to the large number of base areas for transgender to conduct sexual transactions with sex partners. Changing behavior among transgender sex workers is still complicated because of the low use of condoms among transgender women. The study aimed to analyze the relationship between perceptions of vulnerability to contracting HIV with the consistency of using condoms among transgender sex workers to prevent HIV AIDS in the city of Makassar. This type of research was mixed methods research with a quantitative and qualitative approach using a sequential explanatory design (combination model). The quantitative data collection technique used a cross-sectional research design. The qualitative data used in-depth interviews with a research design using case studies to strengthen the quantitative results obtained from HIV-positive transgender sex workers. The number of respondents in this study was 60 people. The results showed a relationship between perceived vulnerability to contracting HIV and the consistency of condom use among transgender sex workers. Islam explicitly states that homosexual and lesbian behavior is a form of deviant sexual behavior contrary to human nature. Sex in Islam is not just to satisfy lust but has an important goal regarding the continuity of life, namely continuing offspring/ reproduction so that same-sex relations are unlikely to produce offspring, so this is not in line with the purpose of sex in Islam.